2007
DOI: 10.1002/hed.20573
|View full text |Cite
|
Sign up to set email alerts
|

Current topics in the epidemiology of oral cavity and oropharyngeal cancers

Abstract: Oral cancer incidence rates rose dramatically during the twentieth century in the United States and Europe, especially among individuals under the age of 60 years. Although influenced by age, sex, and country of origin, incidence trends were most strongly affected by elevated risk among individuals born after approximately 1915. This cohort effect was indicative of strong behavioral influences on oral cancer risk. In this article, associations between oral cancer risk and established behavioral risk factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
184
0
15

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(208 citation statements)
references
References 164 publications
5
184
0
15
Order By: Relevance
“…Infectious agents have been implicated in some cancers of the oral cavity and pharynx, particularly in younger populations (Gillison, 2007). Recent epidemiological and experimental data have implicated infection with human papilloma virus in the pathogenesis of oral cancer; and suggest that about 35 % of all oral cancers are positive for HPV DNA (Kreimer et al, 2005), with 90 to 95 % positive for HPV-16 et al, 2007).…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Infectious agents have been implicated in some cancers of the oral cavity and pharynx, particularly in younger populations (Gillison, 2007). Recent epidemiological and experimental data have implicated infection with human papilloma virus in the pathogenesis of oral cancer; and suggest that about 35 % of all oral cancers are positive for HPV DNA (Kreimer et al, 2005), with 90 to 95 % positive for HPV-16 et al, 2007).…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Alcohol and smoking alone are responsible for 80% of the cases in males, 61% in females and 74% overall (Warnakulasuriya et al, 2005;Gillison, 2007;Petersen, 2009). Lack of awareness of the risk factors among the community (Pakfetrat et al, 2010;Peker and Alkurt, 2010), un-presented early lesions or delayed diagnosis of cancer makes the job even more challenging for the health care provider (Warnakalasuriya et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the comparative epidemiology of HPV infection and associated cancers of the head and neck and cervix, revealed that the global incidence of head and neck SCC and cervical SCC is similar; however, a minority of HNSCC, in comparison to virtually all cervical SCC, are caused by HPV. HPV prevalence is considerably lower in the oral than anogenital region for reasons that are still unclear, in spite of the fact that HPV infection in both sites is strongly associated with sexual behavior [31]. Only a significant fraction of oropharyngeal HNSCC is strongly etiologically associated with HPV infection.…”
Section: Important Differences Between Cervical and Head And Neck Silsmentioning
confidence: 99%